2018
DOI: 10.1111/imm.12950
|View full text |Cite
|
Sign up to set email alerts
|

Segmented filamentous bacteria‐induced immune responses: a balancing act between host protection and autoimmunity

Abstract: SummarySegmented filamentous bacteria (SFB) are Gram-positive, spore-forming, bacteria that primarily colonize the ileum of the small intestine. Upon direct adherence to intestinal epithelial cells, SFB actively stimulate innate and adaptive immune cell activation. The cardinal features of SFBinduced gut immunity -T helper type 17 (Th17) cell differentiation, IgA production and barrier protection -lead to the containment of SFB and further afford protection against invading pathogens. Th17 cells and interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 80 publications
(153 reference statements)
2
55
0
Order By: Relevance
“…However, these variations are overridden by the strong and consistent effect of age, validated through the present study which controlled for these factors. We found that “ Candidatus Savagella” appeared earlier and in higher abundance in BMD and T-Pbx treatment groups, similar to what has been previously found in turkeys (4), and our finding highlights the possible importance of segmented filamentous bacteria such as “ Candidatus Savagella” at priming the immune system and promoting diversification of the healthy microbiome in the gut (21). In the cecum, there is a trend from facultative anaerobes toward a diverse anaerobic bacterial composition, likely reflecting physical changes occurring in the gut during the first weeks of age.…”
Section: Discussionsupporting
confidence: 89%
“…However, these variations are overridden by the strong and consistent effect of age, validated through the present study which controlled for these factors. We found that “ Candidatus Savagella” appeared earlier and in higher abundance in BMD and T-Pbx treatment groups, similar to what has been previously found in turkeys (4), and our finding highlights the possible importance of segmented filamentous bacteria such as “ Candidatus Savagella” at priming the immune system and promoting diversification of the healthy microbiome in the gut (21). In the cecum, there is a trend from facultative anaerobes toward a diverse anaerobic bacterial composition, likely reflecting physical changes occurring in the gut during the first weeks of age.…”
Section: Discussionsupporting
confidence: 89%
“…Recent investigations point to the IL-23/Th17 axis as playing a major role in psoriasis pathogenesis 19 . The adhesion of specific members of gut microbiome to intestinal epithelial cells is found to be essential for the induction of Th17 cells 20 22 . Mice exposed to antibiotics showed inhibition of psoriasis induction by a dysregulation of gut and skin microbiota 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Segmented filamentous bacteria (SFB) are commensal bacteria widely studied for their immune-modulating properties. Flannigan et al demonstrated that SFB colonization has a potent effect in inducing Th17 differentiation, through the stimulation of IL-23 production in dendritic cells, which in turn can activate type 3 innate lymphoid cells (ILC3) to secrete IL-22 [101] (see Innate Lymphoid Cells May Link Microbiota Changes with T Cell Activation). The activation of IL-23/IL-22/IL-17 axis has been recently recognized as a key moment in the acquisition of the inflammatory activity of autoantibodies: in preclinical RA, this axis modulates the glycosylation pattern [102] (see Secretory Immunoglobulins and Aberrant Glycosylation).…”
Section: Humoral Immunity Abnormalities In At-risk Subjectsmentioning
confidence: 99%